Designing an Integrated Ecotourism Package for the 7 Summit Area in Sembalun Lawang, Lombok - Rumba Rumba; Dimas P Dewata; Isna K (Politeknik Pariwisata NHI Bandung, 2026)
Sembalun Lawang Village in East Lombok Regency has great potential to be developed as a community-based ecotourism destination. The region is known for its stunning natural landscape and rich local culture, especially in areas crossed by the 7 Summit Sembalun route, such as Bukit Kondo, Pergasingan, Bukit Anak Dara, and the path to Mount Rinjani. However, until now there has not been an integrated tour package that emphasizes the principle of ecotourism as a whole. This research designs ecotourism-based tour packages that prioritize environmental education and local community empowerment. The method used is a descriptive qualitative-participatory approach with a research and development type of research. Data collection techniques included field observations, in-depth interviews, and documentation studies. Preliminary findings show that there is high interest from tourists in environmentally friendly trekking activities and the readiness of local communities to be more actively involved in tourism management. The final result of this research is an ecotourism tour package model that is integrated and contextualized with local characteristics. The main conclusion states that the development of this package not only supports environmental conservation, but is also able to increase community participation and welfare in Sembalun Lawang Village.